2005
DOI: 10.1016/j.micres.2004.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrients on the production of AK-111-81 macrolide antibiotic by Streptomyces hygroscopicus

Abstract: The influence of different carbon and nitrogen sources on the production of AK-111-81 nonpolyenic macrolide antibiotic by Streptomyces hygroscopicus 111-81 was studied. Substitution of glucose with lactose or glycerol significantly affected maximal antibiotic AK-111-81 productivity as the growth rate was close to that of the basal fermentation medium. Addition of ammonium succinate to the fermentation medium markedly increased the antibiotic productivity as the growth rate was low. Divalent ions as Mn2+, Cu2+,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 14 publications
6
47
0
2
Order By: Relevance
“…In some marine ecosystems, such as the deep sea floor and coral reefs, experts estimate that the biological diversity is higher than in the tropical rainforests (Edward et al, 2006). As marine environmental conditions are extremely different from terrestrial ones, it is surmised that marine actinomycetes have different characteristics from those of terrestrial counterparts, and therefore, might produce different types of bioactive compounds (Fenical et al, 1999;Gesheva et al, 2005). The present study deals with screening for the isolation of actinomycetes to produce antibiotics, isolated from the marine sediments in and around Gokharna and Murudeshwara coastal regions and determination of their antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…In some marine ecosystems, such as the deep sea floor and coral reefs, experts estimate that the biological diversity is higher than in the tropical rainforests (Edward et al, 2006). As marine environmental conditions are extremely different from terrestrial ones, it is surmised that marine actinomycetes have different characteristics from those of terrestrial counterparts, and therefore, might produce different types of bioactive compounds (Fenical et al, 1999;Gesheva et al, 2005). The present study deals with screening for the isolation of actinomycetes to produce antibiotics, isolated from the marine sediments in and around Gokharna and Murudeshwara coastal regions and determination of their antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Basak and Majumdar (1975) reported that kanamycin production by Streptomyces kanamyceticus ATCC 12853 required magnesium sulfate and potassium phosphate (0.4 and 1.0 g L −1 , respectively) and Fe and Zn (0.25 and 0.575 mg mL −1 , respectively), amounts of Mn and Ca did not have any effect, and Cu, Co, Ni, and V have inhibitory effect. Divalent ions as Mn 2+ , Cu 2+ , Fe 2+ stimulated AK-111-81 antibiotic biosynthesis by Streptomyces hygroscopicus 111-81 (Gesheva et al, 2005). The divalent metal ions (Mg, Fe and Mn) sodium dihydrogen phosphate were found essential for bacitracin production by Bacillus licheniformis, whereas Na 2 SO 4 and CaCl 2 decreased the bacitracin yield (Yousaf, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al (2010) made a connection between the rare earth elements scandium and lanthanum and increased activation of the expression of nine genes belonging to nine secondary metabolite-biosynthetic gene clusters of Streptomyces coelicolor A3(2). Investigations on the effect of several metal ions indicated that Cu 2+ , Mn 2+ , and Fe 2+ stimulated AK-111-81 biosynthesis by Streptomyces hygroscopicus, depending on their concentration (Gesheva et al, 2005). Divalent ions stimulated the production of polyenes (Georgieva-Borisova, 1974;Liu et al, 1975;Solivery et al, 1988;Park et al, 1998), and Fe 2+ and Mn 2+ have been found to favor niphimycin production.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial metabolite was produced from Streptomyces sp. LH9 using the sterile fermentation broth as a basal medium, which composed from (g/100 ml distilled water): 2.5% glucose, 0.5% soybean, 0.5% NaCl, 2% K 2 HPO 4 , 0.05% MgSO 4 , and 0.01% CaCO 3 at pH 7 [17].…”
Section: Microorganisms Used In the Studymentioning
confidence: 99%